A Review of the Landslide Monitoring by Using Terrestrial Laser Scanning - Yeak, Zu Ni; Mohd Salleh, Anuar (Recent Trends in Civil Engineering and Built Environment, 2023)
The landslide has been on the rise and has a wide-ranging impact, such as lives lost, structure destruction, road damage, and natural resource depletion. This study aims to determine the advantages and limitations of TLS for monitoring different landslides and identify the applicability of TLS to monitor different landslide movements. The previous research papers are obtained based on the PRISMA guideline and search string. The review found that researchers most use Reigl model scanners due to their high scanning range, and TLS can be used to monitor rockfall, earth slides, earth flow, rockslide, complex, debris flow, and rock topples. However, TLS has difficulties filtering vegetations, scanning the topography of seabed and detecting millimetre scale deformations. Hence, recommendations are proposed to overcome the limitations of TLS.